Answer:
h(x) = -2x^2 -2
Step-by-step explanation:
You know that translating the point (a, b) vertically downward by 3 units will make it be the point (a, b-3).
The same translation works on the point (x, f(x)), or when a=x and b=f(x). Translated downward by 3 units, the point becomes ...
(x, f(x) -3)
You want to name this (x, h(x)), so we have ...
h(x) = f(x) -3
h(x) = -2x^2 +1 -3 . . . substitute the expression for f(x)
h(x) = -2x^2 -2 . . . . . simplify
I would believe you are talking about the Pythagorean Theorem:
In that case the formula is <u>L^2 + L^2 = H^2.</u>
If you have the hypotenuse it is:
<u>H^2 - L^2 = L^2:</u>
When solving, just substitute your lengths for each side of the triangle.
Note: This only works with right triangles.
It will be True
Hope it's help
cx + wx